Empreendimentos econômicos solidários: uma possibilidade de geração de trabalho e renda na perspectiva da inclusão social, Campinas/SP 2011 - Barbosa, Vera Suzart (2011)
The propose of this dissertation is to study two economical solidarity enterprises in Campinas SP: Cooperativa de Reciclagem Tatuapé and the Estandarte de Artesanato Institution. The main objective was to analyze the experience of this two economical solidarity enterprise as a possibility of job and revenue production in order to reach a social inclusion. The work conception, social Exclusion/Inclusion and solidarity economy was adopted as a basic reference using Economy, Sociology, Social Psychology and Social Service in the classic and contemporary authors. As a hypothesis the two economical solidarity enterprises have already studied mean for their participants a possibility to generate job and revenue, it opens the social inclusion that has been constructed in different reach ways and steps. Methodologically the research discuss about a qualitative approach including bibliography, documents, field research and observation. The interview was made with six people from the research, four were from Cooperativa Tatuapé and two were from Grupo Estandarte. The result of this research could affirm the hypothesis considering the particularity of each enterprise, the experience means to the participants a possibility to generate work and revenue in a social inclusion that has been constructed in different steps of citizenship